Development and validation of a critical thinking measurement instrument based on Megapodidae reinwardt bird ecotourism - Yamin, M.; Jufri, A. Wahab; Hakim, Alifman; Gunawan, Gunawan; Sukarso, AA.; Rahmat, Joni (Jurnal Pijar Mipa, 2023)
Critical thinking skills are important in sharing aspects of life in the current and future era of globalization and information. An important aspect of critical thinking is literacy. Literacy abilities within the scope of Natural Sciences refer to scientific literacy. The critical thinking test results show that students' critical thinking components must still be developed. This paper discusses developing and validating a critical thinking measurement instrument for prospective science-biology teacher students based on Megapodidae bird ecotourism. The aim is to develop and assess the validity, reliability, and characteristics of critical thinking skills instruments so that they can be used to measure critical thinking skills in Science-Biology prospective teacher students. Product development in the form of critical thinking skills test instruments in Biology learning for prospective teacher students at FKIP Unram. Instrument development is carried out in four steps: identifying indicators, developing collection items, making validity checks, and improving item quality. Instrument validation is by a learning expert from FKIP Unram. Essay form questions consist of 21 items with difficulty levels at medium and high levels. The results of expert validation analysis using Aiken's V method for each aspect are classified as valid with a value of 0.79. The instrument developed can be used as a valid and reliable measure of critical thinking ability.